A scoping review of the impacts of forest cover dynamics on acari-borne diseases: Beyond forest fragmentation - Nolwenn Blache; Karine Chalvet-Monfray; Christophe Déprés; Serge Morand (Heliyon)
Forest cover has undergone significant changes accelerating over recent decades. Acari vectors such as ticks and chigger mites are intricately linked to forest ecosystems because of the suitable hosts and microclimates provided. However, the implications of forest cover change on Acari vectors and their pathogens remain poorly understood. This study investigates the impacts of forest cover dynamics on Acari-borne diseases risk worldwide through a comprehensive review of the literature.We conducted a scoping review following the PRISMA Method to retrieve citations related to forest cover dynamics and Acari-borne diseases. Eligibility criteria were predefined and relevant data were extracted from selected articles. The analysis employed a descriptive approach and thematic narrative synthesis.Our review revealed that the influence of forest cover dynamics on Acari-borne diseases and vectors was predominantly discussed within a Western context, especially regarding Ixodes ticks and Lyme disease. Four types of forest cover dynamics have been identified in the literature: deforestation, fragmentation, conversion and reforestation. However, there was no consensus on their impacts on vectors and pathogens. Studies reported conflicting findings including: protective or risk effects, nonlinear relationships, dependent effects influenced by additional factors altering relationships or no significant effects. Although, there is limited empirical evidence on tropical contexts as well as for reforestation and conversion dynamics. Differences in results trends emerge according to the article type, with literature reviews often overestimating the dilution effect, which assumes that species diversity reduces disease risk, observed in empirical research. Finally, our review identifies a notable absence of studies on scrub typhus.This scoping review provides a novel and comprehensive overview of global literature on the impacts of forest cover dynamics on Acari vectors and the infectious agents they transmit. It highlights the need for future research targeting specific forest cover dynamics on chigger mite vectors in a tropical context.